2015
DOI: 10.1016/j.neuron.2015.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Lateral Habenula and Anterior Cingulate Cortex in Negative Outcome Monitoring and Behavioral Adjustment in Nonhuman Primates

Abstract: Animals monitor the outcome of their choice and adjust subsequent choice behavior using the outcome information. Together with the anterior cingulate cortex (ACC), the lateral habenula (LHb) has recently attracted attention for its crucial role in monitoring negative outcome. To investigate their contributions to subsequent behavioral adjustment, we recorded single-unit activity from the LHb and ACC in monkeys performing a reversal learning task. The monkey was required to shift a previous choice to the altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 63 publications
8
98
0
Order By: Relevance
“…Instead, macaques with mPFC lesions exhibit a slight deficit in the ability to maintain the correct response following a reversal (Chudasama et al, 2013). This also fits with a recent neurophysiology study showing the neurons in the anterior cingulate cortex track rewarded and unrewarded choices over multiple trials during reversal learning (Kawai et al, 2015). Thus, the mPFC may have a more circumscribed role in reversal than the OFC, one that primarily manifests in tasks with a high demand on attention and performance monitoring; consistent with ideas about the involvement of the mPFC in stimulus detection, timing, and error detection (Laubach et al, 2015).…”
Section: Neural Substrates Of Reversalsupporting
confidence: 90%
“…Instead, macaques with mPFC lesions exhibit a slight deficit in the ability to maintain the correct response following a reversal (Chudasama et al, 2013). This also fits with a recent neurophysiology study showing the neurons in the anterior cingulate cortex track rewarded and unrewarded choices over multiple trials during reversal learning (Kawai et al, 2015). Thus, the mPFC may have a more circumscribed role in reversal than the OFC, one that primarily manifests in tasks with a high demand on attention and performance monitoring; consistent with ideas about the involvement of the mPFC in stimulus detection, timing, and error detection (Laubach et al, 2015).…”
Section: Neural Substrates Of Reversalsupporting
confidence: 90%
“…Although we have cast proactive control as one of several functions of ACC (Kawai et al, 2015), we do not claim that proactive control is solely driven by ACC, as indeed there is evidence that proactive control can be exerted by a network of other regions (Marini et al, 2016;MacDonald, Cohen, Stenger, & Carter, 2000). Perhaps the closest computational model to the PRO-control model is a recent model of dual control processes (Ziegler et al, 2014).…”
Section: Proactive Versus Reactive Mechanisms Of Controlmentioning
confidence: 86%
“…The PRO-control model provides a new degree of mechanistic clarity to the notions of proactive and reactive control signals, which have been explored both theoretically (Aron, 2011;Braver et al, 2007;De Pisapia & Braver, 2006) and empirically (Marini, Demeter, Roberts, Chelazzi, & Woldorff, 2016;Kawai, Yamada, Sato, Takada, & Matsumoto, 2015). Although we have cast proactive control as one of several functions of ACC (Kawai et al, 2015), we do not claim that proactive control is solely driven by ACC, as indeed there is evidence that proactive control can be exerted by a network of other regions (Marini et al, 2016;MacDonald, Cohen, Stenger, & Carter, 2000).…”
Section: Proactive Versus Reactive Mechanisms Of Controlmentioning
confidence: 90%
“…The win-stay and lose-shift results in particular suggest that the LHb is critical for monitoring the current behavior on a trial by trial basis to inform future decisions. In monkeys, neurons recorded from the LHb in a saccade based version of probabilistic reversal learning showed short latency responses to outcomes that were not modulated by the number of consecutive reward experiences (either positive or negative) that the monkey had experienced (Kawai et al 2015). These neural results support the hypothesis that the LHb is sensitive to trial by trial changes in outcome expectations, an idea that is consistent with those found from both reversal learning and subjective decision making inactivation studies outlined above.…”
Section: Lhb Contributions To Behavioral Flexibilitymentioning
confidence: 99%
“…Both outcomes and the cues that predict them are signaled in the LHb and seem to represent valence on a trial by trial basis (Kawai et al 2015). Other studies have suggested that the LHb monitors specific behaviors in complex environments to guide choices (Stopper and Floresco 2014; Baker et al 2015).…”
Section: Introductionmentioning
confidence: 99%